Cover Image: Volume 34 Issue 9. Issue 9 (6th September 2019) - Endo, Daisuke; Yamamoto, Taira; Kuwaki, Kenji; Kajimoto, Kan; Amano, Atsushi
Abstract : Front Cover Caption : The cover image is based on the Original Article Neointima on the scar site atier the letiatrial appendage amputation by Daisuke Endo et al., https://doi.org/10.1111/jocs.14127